PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS PROBLEM BASED LEARNING DIPADU THINK PAIR SHARE UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Abu Husen; Sri Endah Indriwati; Umie Lestari (BIOEDUKASI, 2017)
This study aims to develop a teaching materials of biology ubjects based on problem based learning combined by think pair share models that used in teaching circulation system at the 11th grades of natural science senior high school to improve students' science process skills. The development in this study following steps of 4D model (Define, Design, Develop, and Disseminate) that developed by Thiagarajan. In this development study the teaching material just followed three steps until validation product at Develop phase. The teaching materials that developed in this study consist of syllabi, lesson plans, worksheets, and assessment sheet. Validation assessment was done by two lectures as education expert and content material expert from Universitas Negeri Malang and a teacher as practitioner expert from SMAN 1 Kasiman Bojonegoro. Validation by education expert shows the value of validity is 94.03, the validation by content material expert shows the value of validity is 91.50, and the result of the validation by practitioners shows the value of validity is 95.08. Based on the validation results of the three experts indicate that the teaching materials achieve very valid criteria that’s mean did not need to revision and can be be used in biology learning of circulation system to improve students' science process skills of the 11th grades of natural science senior high school. Keywords: problem based learning, think pair share, science process skills.